Global Tensor‐Matter Transitions in F‐Theory. Issue 7 (26th June 2018) - Dierigl, Markus; Oehlmann, Paul; Ruehle, Fabian
Abstract: We use F‐theory to study gauge algebra preserving transitions of 6d supergravity theories that are connected by superconformal points. While the vector multiplets remain unchanged, the hyper‐ and tensor multiplet sectors are modified. In 6d F‐theory models, these transitions are realized by tuning the intersection points of two curves, one of them carrying a non‐Abelian gauge algebra, to a (4, 6, 12) singularity, followed by a resolution in the base. The six‐dimensional supergravity anomaly constraints are strong enough to completely fix the possible non‐Abelian representations and to restrict the Abelian charges in the hypermultiplet sector affected by the transition, as we demonstrate for all Lie algebras and their representations. Furthermore, we present several examples of such transitions in torically resolved fibrations. In these smooth models, superconformal points lead to non‐flat fibers which correspond to non‐toric Kähler deformations of the torus‐fibered Calabi‐Yau 3‐fold geometry. Abstract : The F‐theory is used to study gauge algebra preserving transitions of 6d supergravity theories that are connected by superconformal points. While the vector multiplets remain unchanged, the hyper‐ and tensor multiplet sectors are modified. In 6d F‐theory models, these transitions are realized by tuning the intersection points of two curves, one of them carrying a non‐Abelian gauge algebra, to a (4, 6, 12) singularity, followed by a resolution in the base. The six‐dimensional supergravity anomaly constraints are strong enough to completely fix the possible non‐Abelian representations and to restrict the Abelian charges in the hypermultiplet sector affected by the transition, as is demonstrated for all Lie algebras and their representations. Furthermore, several examples of such transitions in torically resolved fibrations are presented. In these smooth models, superconformal points lead to non‐flat fibers which correspond to non‐toric Kähler deformations of the torus‐fibered Calabi‐Yau 3‐fold geometry.